Bibliography for All: G. Thomas Tanselle’s Descriptive Bibliography, Charlottesville: The Bibliographical Society of the University of Virginia, 2020 - St. Onge, Ruth-Ellen (Mémoires du livre / Studies in Book Culture, 2026)
In this essay, the author reviews G. Thomas Tanselle’s Descriptive Bibliography (2020), a retrospective collection of essays by the influential scholar and editor who defines key concepts of descriptive bibliography while providing a methodological approach to topics including format, paper, typography and bindings of books from a range of historical periods. St. Onge singles out Tanselle’s innovations in the description of publishers’ bindings and dust jackets and identifies the essay “Format” as being representative in demonstrating Tanselle’s rigorous standards. Written over the course of several decades, some of the essays are dated, but overall, Tanselle’s work is well placed to inform the work of scholars seeking to expand the scope of descriptive bibliography, traditionally Anglo-American in focus. St. Onge concludes the review by considering the future of descriptive bibliography as a discipline.